2015
DOI: 10.17265/2159-581x/2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Design of Metering Device Key Parts of Pneumatic Grass Seeder

Abstract: Based on the mechanical and physical properties study of forage grass seeds, multi-line with one-device type metering device was designed. It was composed of adjustable screw, stirrer, metering device housing and central metering sheave and so on. The sowing rate can be set by turning the screw to change the working length of the central metering sheave relative to the metering device housing. The stirrer inside of the sheave housing is used to prevent seeds overhead. And metering of different sizes of seed is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Mishra et al, (2015) modified these cups to a shape which was cylindrical at top and conical at the bottom for better retention of seeds of crops like groundnut, paddy and green gram. The arc-shaped grooves over the periphery of cylinder were developed for metering of bothsmall and large seeds (Gaixia et al, 2015). For small seeds, the groove was shallow and the number of grooves was more, while metering big seeds, the depth of the groove was decreased up to not less than half the thickness of the seed in order to reduce the damage to seed.…”
Section: Issn: 2319-7706 Volume 7 Number 03 (2018)mentioning
confidence: 99%
“…Mishra et al, (2015) modified these cups to a shape which was cylindrical at top and conical at the bottom for better retention of seeds of crops like groundnut, paddy and green gram. The arc-shaped grooves over the periphery of cylinder were developed for metering of bothsmall and large seeds (Gaixia et al, 2015). For small seeds, the groove was shallow and the number of grooves was more, while metering big seeds, the depth of the groove was decreased up to not less than half the thickness of the seed in order to reduce the damage to seed.…”
Section: Issn: 2319-7706 Volume 7 Number 03 (2018)mentioning
confidence: 99%
“…It receives and fabricates the obtained data through the control system to send a voltage to a mounted DC motor with the rotating shaft to drop seeds through the tube seed. Gaixia et al (2015) designed a metering device of a pneumatic seeder, they reported that the metering device is mainly composed of an adjustable screw rod, sprocket wheel, Stirring teeth, regulating mechanism and casing body. It takes its motion from the machine land wheel.…”
Section: Introductionmentioning
confidence: 99%